Tamm-Horsfall Glycoprotein Enhances PMN Phagocytosis by Binding to Cell Surface-Expressed Lactoferrin and Cathepsin G That Activates MAP Kinase Pathway - Chia-Li Yu; Chang-Youh Tsai; Ming-Chi Lu; Cheng-Han Wu; Syue-Cian Siao; Song-Chou Hsieh; Ko-Jen Li (Molecules, 2011)
The molecular basis of polymorphonuclear neutrophil (PMN) phagocytosis-enhancing activity (PEA) by human purified urinary Tamm-Horsfall glyco- protein (THP) has not been elucidated. In this study, we found human THP bound to lactoferrin (LF) and cathepsin G (CG) expressed on the surface of PMN, identified by a proteomic study with MALDI-TOF- LC/LC/mass spectrometric analysis. Pre-incubation of 10% SDS-PAGE electrophoresed PMN lysates with monoclonal anti-LF or anti-CG antibody reduced the binding with THP. To elucidate the signaling pathway of THP on PMN activation, we found THP enhanced ERK1/2 phosphorylation, reduced p38 MAP kinase phosphorylation, but had no effect on DNA binding of the five NF-kB family members in PMN. To further clarify whether the carbohydrate-side chains or protein-core structure in THP molecule is responsible for THP-PEA, THP was cleaved by different degrading enzymes with carbohydrate specificity (neuraminidase and β-galactosidase), protein specificity (V8 protease and proteinase K) or glycoconjugate specificity (carboxylpeptidase Y and O-sialoglycoprotein endopeptidase). We clearly demonstrated that the intact protein-core structure in THP molecule was more important for THP-PEA than carbohydrate-side chains. Putting these results together, we conclude that THP adheres to surface-expressed LF and CG on PMN and transduces signaling via the MAP kinase pathway to enhance PMN phagocytosis.